Layers of Loss: Overt and Subtle forms of Abandonment in Douglas Stuart’s - Shuggie Bain; Sameeul Haq Nazki (MultiTech Publisher, 2024)
This paper delves into the complex theme of loss and abandonment in Douglas Stuart’s Shuggie Bain. The novel is set against the backdrop of 1980s Glasgow, grappling with economic decline and social disintegration. The novel paints a vivid portrait of overt abandonment, such as parental desertion, and subtle forms, like emotional neglect and societal indifference. Through the lens of young Shuggie Bain, Stuart intricately captures the impact of his father’s absence and his mother Agnes’s struggle with alcoholism. He illustrates how these direct forms of abandonment fracture the family’s stability and Shuggie’s childhood. Stuart goes beyond the obvious, layering his narrative with subtler portrayals of abandonment. He concentrates on the emotional withdrawal of community members numbed by poverty and the internal conflicts within Shuggie household. By focusing on these layered experiences, this paper investigates how Stuart illuminates the personal traumas of his characters. He also critiques broader social issues, including economic disenfranchisement, addiction, and the erosion of communal bonds. The analysis underscores how Stuart employs abandonment as a recurring motif to explore the disintegration of both individual lives and social fabric. This paper argues that the overlapping experiences of loss in Shuggie Bain offer a profound exploration of resilience and the human capacity to find hope amidst pervasive despair. It reveals the indelible marks that abandonment leaves on identity, relationships, and community